Absolute substrate oxidation rates are lower in older adults with amnestic mild cognitive impairment - Nicholas A. Rizzi; Mary K. Kramer; Theodore M. DeConne; James M. Ellison; Alyssa M. Lanzi; Matthew L. Overstreet; David G. Edwards; Matthew L. Cohen; Curtis L. Johnson; Christopher R. Martens (Physiological Reports)
Abstract Previous studies in individuals with mild cognitive impairment suggest that they may have altered systemic metabolic function at rest; however, metabolic function during aerobic exercise is not fully understood in this population. This study sought to determine whether individuals with amnestic mild cognitive impairment (aMCI) have lower rates of baseline and peak fat oxidation (FatOx) during a graded exercise test (GXT) compared with cognitively unimpaired control participants (CU). Twenty‐two (22) older adults with aMCI and 21 age‐ and sex‐matched adults completed a GXT to assess rates of substrate oxidation and peak oxygen consumption (VO2 peak). Rates of FatOx and carbohydrate oxidation (CHOOx) were assessed using VO2 and VCO2. Resting absolute (0.10 ± 0.03 vs. 0.09 ± 0.02 g/min, p = 0.126) and relative (1.5 ± 0.43 vs. 1.4 ± 0.44 mg/kg/min, p = 0.492) rates of FatOx, as well as resting absolute (0.51 ± 0.11 vs. 0.59 ± 0.15 g/min, p = 0.093) and relative (8.0 ± 2.3 vs. 7.5 ± 2.7 mg/kg/min, p = 0.126) rates of CHOOx were similar between groups. However, peak absolute rates of FatOx (0.33 ± 0.13 vs. 0.39 ± 0.10 g/min, p = 0.033) and CHOOx (1.9 ± 0.41 vs. 2.2 ± 0.49 g/min, p = 0.046) were significantly lower in the aMCI group. Time to fatigue (7.2 ± 2.0 vs. 8.7 ± 2.3 min, p = 0.033) and absolute VO2 peak (1.3 ± 0.34 vs. 1.6 ± 0.47 L/min, p = 0.024) were also significantly lower in the aMCI group. These findings suggest that absolute peak rates of whole‐body FatOx and CHOOx are reduced during aerobic exercise in older adults with aMCI.